Valores pessoais e valores organizacionais: a busca do alinhamento - Silva Filho, Luiz Sebastião da (2014)
This study presents a discussion about the alignment of personal and organizational values, as a promoter of engagement in work and social welfare, from the perspective afforded by the so-called knowledge society. Be regarded as hypothesis the idea that the alignment of values can promote gains on productivity in the enterprises, achieving the professional and the common good. For this, we performed a literature search, in search of better understanding and delineation of concepts and issues related to motivation, organizational culture and engagement at work. It also dealt with the mismatch between the stated organizational values and effectively practiced by organizations and their impact on society and human rights. Moreover, it also presented a methodology for mapping personal and organizational values performed in various organizations. At the end, we found that the knowledge and information society, there is a great potential represented by individuals and citizens willing to undertake effort, talent and engagement in causes and values that are identified either as employees in an organization or consumers of goods and services towards a better society and a sustainable future